The Influence Of Lifestyle And Brand Image On The Purchasing Decision Of Wardha Cosmetics Among Students Of The Faculty Of Economics, Gunung Rinjani University Class Of 2021-2024 - Luthfi, Ashwatul; Sulkiah, Sulkiah (Universitas Hamzanwadi, 2025)
The purpose of this study is to ascertain and examine how lifestyle and brand perception affect Wardah cosmetics purchases made by Gunung Rinjani University's Faculty of Economics students in the 2021–2024 academic year. This kind of study is associated with a quantitative methodology. Questionnaires were distributed to 427 students as part of the data collection process. This study's sampling strategy used the Slovin formula, yielding a sample of 81 pupils. The findings of this study demonstrate that lifestyle exerts neither a positive nor a significant impact on the purchasing decisions of Wardah cosmetics among students at the Faculty of Economics, Gunung Rinjani University, as the T-statistic value is less than the T-table value, specifically 0.374 < 1.96, with a p-value of 0.709 > 0.05. Brand Image exerts a positive and significant impact on purchasing decisions, evidenced by a p-value of 0.00 (less than 0.05) and a T-statistic of 9.296 (more than the T-table value of 1.96).